2011
DOI: 10.1371/journal.pone.0026180
|View full text |Cite
|
Sign up to set email alerts
|

Infection of XC Cells by MLVs and Ebola Virus Is Endosome-Dependent but Acidification-Independent

Abstract: Inhibitors of endosome acidification or cathepsin proteases attenuated infections mediated by envelope proteins of xenotropic murine leukemia virus-related virus (XMRV) and Ebola virus, as well as ecotropic, amphotropic, polytropic, and xenotropic murine leukemia viruses (MLVs), indicating that infections by these viruses occur through acidic endosomes and require cathepsin proteases in the susceptible cells such as TE671 cells. However, as previously shown, the endosome acidification inhibitors did not inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 47 publications
4
33
1
Order By: Relevance
“…Instead, the effect of the F183L mutation was measured in a series of APJ activity assays since variations in receptor interactions and especially internalization previously have been shown to influence viral infectivity (5,15). These APJ activity assays showed that the F183L mutation results in decreased APJ affinity, as well as a decreased ability to activate APJ upon binding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, the effect of the F183L mutation was measured in a series of APJ activity assays since variations in receptor interactions and especially internalization previously have been shown to influence viral infectivity (5,15). These APJ activity assays showed that the F183L mutation results in decreased APJ affinity, as well as a decreased ability to activate APJ upon binding.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, interactions with apelin-13 result in recycling of the receptor, whereas binding of apelin-36 results in degradation of the receptor (22,26). These differences in the fate of the receptor might influence viral infectivity since studies have shown the internalization of virus through specific cellular compartments to be important for infectivity (5,15). Krueger and Albritton have previously shown that a chimeric MLV Env protein expressing the somatostatin ligand changes infectivity according to the somatostatin receptor variant used for internalization because of variations in receptor internalization through different cellular compartments (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it had been reported that ammonium chloride inhibits ecotropic MLV infection but does not amphotropic and xenotropic MLV infections, showing that ecotropic MLV infection occurs through acidic vesicles, but amphotropic and xenotropic MLV infections do not [49,50] (Table 2). The more specific inhibitors of endosome acidification (concanamycin A and bafilomycin A-1) suppress all of ecotropic, amphotropic, polytropic, and xenotropic MLV infections [51,52]. At present, it is generally accepted that ecotropic MLV infection requires acidification, because all the studies consistently reported the suppression of ecotropic virus replication with the inhibitors of endosome acidification.…”
Section: Ph-dependent Retrovirus Infectionmentioning
confidence: 99%